Potensi dan Daya Saing Ekspor Produk Lokal Indonesia di Pasar China - Raviadi, Krista Amanda; Imaningsih, Niniek (Jurnal Ilmiah Wahana Pendidikan, 2023)
International trade in the form of exports and imports can benefit the 2 countries that are mutually concerned and can be a form of cooperation and communication between countries. This study uses a descriptive qualitative approach to find out whether the superior commodities that can be exported to China, whether these commodities have potential and have competitiveness in the Chinese market. The results of this study show that several commodities in Indonesia are the most exported to China, but do not necessarily have the potential and competitiveness in the Chinese market.